Assessing the turkish “trading state” in sub-saharan africa - (:unkn) unknown (Palgrave Macmillan, 2020)
This study scrutinizes Turkey as a trading state in sub-Saharan Africa (SSA) by analysing both the benefits and limitations of this role. Given the linkage between trade and foreign policy, this study will also examine how Turkey’s foreign policy achievements in SSA have impacted its trading state in terms of its instruments, geographical focus, and sectors. In light of this, the paper first attempts to review the conceptual framework of Rosecrance’s trading state with the aim of understanding the linkage between the “Trading State” and foreign policy. In doing so, it aims to locate trade versus conquest from the perspective Rosecrance and questions whether Rosecrance’s trading state is now in decline in face of the military/security state. Secondly, the paper reviews the Turkish trading state since the 1990s and showcases the strengths and weaknesses of Turkey’s trading state strategy. Thirdly, it tries to assess whether Turkey shows the characteristics of a real trading state in the context of sub-Saharan Africa. Here, Turkey’s achievements and challenges in terms of trade relations with sub-Saharan countries will be detailed based on the Turkish foreign policy-trade nexus in SSA and the Turkish trading state’s instruments, geographical focus, sectors, and benefits and limitations, respectively. © 2020, The Author(s).
Keywords: Foreign policy; Military state; Sub-Saharan africa; Trading state; Turkey